Living life with cerebral palsy? A description of the social safety nets for individuals with cerebral palsy in the Nordic countries. Issue 6 (August 2021) - Alriksson-Schmidt, Ann I.; Jeglinsky, Ira; Jonsdottir, Gudny; Kedir Seid, Abdu; Klevberg, Gunvor; Buschmann, Eva; Jahnsen, Reidun
Aims: This report reviews major laws, acts and regulations of social benefits and services for individuals with disabilities, focusing on cerebral palsy in the five Nordic countries. It summarizes the available benefits and services and the re-application process and provides comparative analyses among the countries. Methods: Published reports, articles and relevant government and municipal websites were reviewed for each respective country and used to compile an overview and comparison between the countries. Results: In the Nordic countries, there are a number of laws and regulations in place to support individuals with cerebral palsy and their families. In addition, there are numerous social benefits available for which individuals with disabilities can apply. Although there are national differences, the similarities across the five countries regarding laws, social benefits offered for individuals with cerebral palsy and the application processes are clear. However, the application processes seem cumbersome and, at times, redundant. Physicians and other healthcare specialists repeatedly need to write 'medical certificates' describing the diagnosis and its consequences for a disability that is chronic and lifelong. Conclusions: Participation in society for individuals with cerebral palsy disabilities can be enabled by social benefits. By extension, social benefits may indirectly have implications for public health in individuals with disabilities. Although the lives of individuals with cerebral palsy – as with others – can improve in certain areas, the need for social benefits will generally increase, not decrease, over time. Although it is clearly important to have checks and balances that prevent system misuse, it might be worthwhile from a cost-benefit perspective to investigate whether the current systems could be improved to better manage time and resources and avoid emotional distress by streamlining the application process.